Manifestations of phaticity in podcast interaction: A discursive-integrative emic- epistemological pragmatic analysis within an ostensive-inferential framework - Noviance, Kristina Marta; Rahardi, R. Kunjana (BAHASTRA, 2026)
This study investigates the manifestations and pragmatic meanings of phaticity in podcast interactions through a discursive-integrative emic–epistemological pragmatic approach grounded in the ostensive–inferential framework. The research aims to uncover how phatic practices are produced, interpreted, and function interactionally within contemporary podcast discourse. The data consist of podcast utterances that exemplify various forms of phatic communion in natural language use. The substantive data source comprises podcast discourse containing identifiable phatic elements, while the locational data source includes a range of podcasts accessed throughout the research period. Data were collected using a non-participatory observation method, specifically through close and repeated listening to the selected podcast episodes. A systematic note-taking technique was employed to document relevant phatic expressions, enabling effective data organization, categorization, and analytical traceability. Data collection was deemed complete once all instances had been exhaustively classified into analytically relevant types serving as the basis for interpretation. Data analysis was conducted using a contextual pragmatic method that integrates conventional context and virtual context, with particular attention to the multimodal cybertextual environment of podcast interactions. In line with the principles of third-wave pragmatics, the analysis also incorporates social, societal, and cultural dimensions, emphasizing participants’ emic perspectives while maintaining epistemological rigor. The analytical procedure involved data identification, classification or reduction, pragmatic interpretation, and systematic presentation of findings. The findings reveal three dominant manifestations of pragmatic meanings of phaticity in podcast interactions: (1) greeting-related phatic meanings, functioning to initiate and sustain interpersonal engagement; (2) humor-related phatic meanings, serving to build rapport and interpersonal alignment; and (3) emphasis-related phatic meanings, which reinforce attentiveness and interactional involvement. These findings demonstrate that phaticity in podcast discourse operates as a dynamic pragmatic resource shaped by inferential intentions, discursive context, and digitally mediated interaction.